Photochemical Grafting of Organic Alkenes to Single-Crystal TiO2 Surfaces: A Mechanistic Study - Franking, Ryan; Kim, Heesuk; Chambers, Scott A.; Mangham, Andrew N.; Hamers, Robert J. (AMER CHEMICAL SOC, 2012)
The UV-induced photochemical grafting of terminal alkenes has emerged as a versatile way to form molecular layers on semiconductor surfaces. Recent studies have shown that grafting reactions can be initiated by photoelectron emission into the reactant liquid as well as by excitation across the semiconductor band gap, but the relative importance of these two processes is expected to depend on the nature of the semiconductors, the reactant alkene and the excitation wavelength. Here we report a study of the wavelength-dependent photochemical grafting of alkenes onto single-crystal TiO2 samples. Trifluoroacetamide-protected 10-aminododec-1-ene (TFAAD), 10-N-BOC-aminodec-1-ene (t-BOC), and 1-dodecene were used as model alkenes. On rutile (110), photons with energy above the band gap but below the expected work function are not effective at inducing grafting, while photons with energy sufficient to induce electronic transitions from the TiO2 Fermi level to electronic acceptor states of the reactant molecules induce grafting. A comparison of rutile (110), rutile (001), anatase (001), and anatase (101) samples shows slightly enhanced grafting for rutile but no difference between crystal faces for a given crystal phase. Hydroxylation of the surface increases the reaction rate by lowering the work function and thereby facilitating photoelectron ejection into the adjacent alkene. These results demonstrate that photoelectron emission is the dominant mechanism responsible for grafting when using short-wavelength (similar to 254 nm) light and suggest that photoemission events beginning on mid-gap states may play a crucial role.
Keywords: EXCITON-MEDIATED HYDROSILYLATION; ANATASE TIO2; WORK FUNCTION; BIOMOLECULAR INTERFACES; DIAMOND SURFACES; OXIDE SURFACE; TRAPPED HOLES; RUTILE; ADSORPTION; SILICON